1992
DOI: 10.1161/01.res.71.3.701
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of interdependence between extra-alveolar arteries and lung parenchyma in piglets.

Abstract: Mechanical interdependence between intrapulmonary structures and parenchyma has not been studied previously in immature postnatal lungs. To study these interactions, lung elastic moduli were measured by pressure-volume and punch indentation studies in lobes excised from 3-day-old (n = 6), 1-month-old (n = 6), and 3-month-old (n = 7) piglets. After extra-alveolar arteries were filled with a radiopaque fluid silicone compound, transpulmonary pressure and arterial pressure were varied independently as the lobar v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Two groups of female Duroc piglets were studied: one 3-7 days of age (1.3-2.1 kg body wt), which was designated the "immature" group, and the other 3 mo of age (25-40 kg body wt), which was designated the "mature" group. Age of the immature group was chosen to avoid temporary characteristics of structure and function in freshly newborn piglet lungs (23). Age of the mature group was chosen to avoid the practical difficulties in handling large, fully grown pigs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups of female Duroc piglets were studied: one 3-7 days of age (1.3-2.1 kg body wt), which was designated the "immature" group, and the other 3 mo of age (25-40 kg body wt), which was designated the "mature" group. Age of the immature group was chosen to avoid temporary characteristics of structure and function in freshly newborn piglet lungs (23). Age of the mature group was chosen to avoid the practical difficulties in handling large, fully grown pigs.…”
Section: Methodsmentioning
confidence: 99%
“…Because elastic moduli of the lung parenchyma are also similar in the two age groups, it was concluded that local features of airway-parenchyma coupling limited the generation of local parenchymal recoil around bronchi in the immature lungs. lung growth; airway-parenchyma interdependence; bronchograms A PREVIOUS STUDY DOCUMENTED remarkable behavior of extra-alveolar blood vessels during inflation of excised immature piglet lungs (23). Lung inflation compressed these vessels, in contrast to the decompression that had been observed consistently during inflation of excised mature lungs from several species (1,13,17,29,33).…”
mentioning
confidence: 99%
“…However, the transpulmonary pressure and lung volume at which airway closure occurs is dependent on the forces applied to bronchi, for example from parenchymal interdependence, as well as the mechanical properties of the bronchi themselves [18][19][20][21]. Elastic recoil pressures of immature lungs are low compared to adults [19,21,24], suggesting that the forces resisting bronchial closure may be less in the infant than the adult.…”
Section: Pressure Induced Airway Closurementioning
confidence: 99%
“…The lung maturation in piglets at birth is advanced compared with human newborns. The airways and associated blood vessels are completely formed at birth, whereas parenchymal development occurs primarily after birth (26). In contrast to the human newborn the chest wall of the newborn piglet is stiff (27).…”
Section: Discussionmentioning
confidence: 99%